Evolução das exportações e de seus determinantes nos BRICS (Brasil, Rússia, Índia, China e África do Sul), nas últimas três décadas - Carvalho, Vinicius Spirandelli (2009)
The dissertation has the main goal to investigate the performance of the exports sector for a set of selected emerging economies: Brazil, Russia, India, China and South Africa and to identify its main determinants. The econometric investigation based on the variance decomposition analysis has shown that capital flows (FDI) are relevant to understand export performance for all five countries; technological effort result (patents) is important for Russia, India and China; investment rate for Brazil and South Africa; exchange rate for Brazil, Russia, India and South Africa; the proxy for growth of the main partners is crucial for chinese exports; and finally, education seems to matter for brazilian exports. The estimated exports VEC models for Brazil, India China and South Africa indicate that capital flows (FDI) are relevant for the short run adjustment (Brazil) and on the long run for the other economies. Other than this, the real exchange rate is statistically significant in the long run (evidence of cointegration) for Brazil and South Africa, and for short run adjustments in China. The proxy for foreign growth of the main trade partners (TCPPC) is relevant both in the short and the long run for India and Brazil, while we used the world growth for South Africa, which is relevant for both time horizons. Finally, education is an important variable in the long run for Brazil, while patents is relevant for China, India and South Africa. In general, one can say that there is a relatively large set of variables that are not necessarily homogeneous among the BRICS when analyzing exports performance over the past decades.